Design of a Tunable Self‐Oscillating Polymer with Ureido and Ru(bpy)3 Moieties. (7th July 2017) - Masuda, Tsukuru; Shimada, Naohiko; Sasaki, Taira; Maruyama, Atsushi; Akimoto, Aya Mizutani; Yoshida, Ryo
Abstract: An upper critical solution temperature (UCST)‐type self‐oscillating polymer was designed that exhibited rhythmic soluble–insoluble changes induced by the Belousov–Zhabotinsky (BZ) reaction. The target polymers were prepared by conjugating Ru(bpy)3, a catalyst for the BZ reaction, to ureido‐containing poly(allylamine‐co‐allylurea) (PAU) copolymers. The Ru(bpy)3 ‐conjugated PAUs exhibited a UCST‐type phase‐transition behavior, and the solubility of the polymer changed in response to the alternation in the valency of Ru(bpy)3 . The ureido content influences the temperature range of self‐oscillation, and the oscillation occurred at higher temperatures than conventional LCST‐type self‐oscillating polymers. Furthermore, the self‐oscillating behavior of the Ru‐PAU could be regulated by addition of urea, which is a unique tuning strategy. We envision that novel self‐oscillating polymers with widely tunable soluble‐insoluble behaviors can be rationally designed based these UCST‐type polymers.